Revisiting the three delays model: Persistent drivers of obstetric fistula in sub‐Saharan Africa during the era of maternal health interventions - Ahmed Abdinasir Abdulle; Ilyas Abdullahi Khalif; Aniso Mohamed Abdi; Yusuf Hared Abdi; Mohamed Abdirahim Omar; Sharmake Gaiye Bashir (International Journal of Gynecology & Obstetrics, 2026)
Abstract Obstetric fistula remains one of the most preventable yet persistent forms of maternal morbidity in sub‐Saharan Africa (SSA), despite major investments in maternal health services. Traditionally associated with prolonged obstructed labor and delayed access to emergency obstetric care, fistula continues to expose failures across the continuum of care. This narrative review critically reassesses the contemporary relevance of the Three Delays Model as an explanatory framework for persistent obstetric fistula in SSA. A structured search of PubMed, Scopus, Web of Science, and Google Scholar identified literature published between 2000 and 2026, with 74 sources included in the final synthesis. Findings indicate that all three delays remain influential but have evolved in important ways. Delay 1 is increasingly shaped by structural poverty, gender inequality, and constrained decision‐making autonomy. Delay 2 persists through geographic isolation, insecurity, weak transport systems, and referral failures. Delay 3 has become increasingly prominent, driven by shortages of skilled personnel, inadequate infrastructure, delayed intervention, and rising iatrogenic fistula linked to unsafe obstetric surgery. Preventing fistula now requires moving beyond service contact indicators toward quality centered, equity focused, and context sensitive maternal health system reforms.